A scoring system for the foot and ankle that is acceptable, reliable, valid and responsive - Dawson, J; Boller, I; Doll, H; Jenkinson, C; Lavis, G; Sharp, R; Cooke, P (2012)
We read with interest the recent paper by Groarke et al. (Quality of life in individuals with chronic foot conditions: a cross sectional observational study. The Foot (2012) doi:10.1016/i.foot.2011.11.007). The paper ended by stating that 'there is no scoring system for the foot and ankle that is valid, repeatable and reliable'. This statement is misleading. The authors could have made reference to the patient-reported Manchester-Oxford Foot Questionnaire (MOXFQ). The MOXFQ has been subjected to more rigorous testing of its measurement properties than is the case for most instruments, and has been demonstrated to be acceptable, reliable, valid and responsive in the context of foot or ankle surgery. © 2012.